Bequests, Imperfections in Factor Markets, and Long-Run Inequality: A Theoretical Assessment of Piketty - Zuleta, Hernando; Alvarez, Andres; Gomez, Camilo (Journal of Income Distribution®, 2024)
The book Capital in the Twenty-First Century by Thomas Piketty (2014) has renewed the public and scholar debate about wealth and income inequality. Theoretical critiques have focused their attention on a regularity pointed out by the author, namely, the growth rate of the economy is lower than the interest rate, r > g. However, two other relevant insights are key to understand the persistence of inequality: bequests and differences between factor prices and the marginal productivity of factors. We present an OLG model that incorporates these two elements and explores under which circumstances inequality between two social groups, rich and poor dynasties, is a long-term equilibrium result in a growing economy. Our model considers two goods, one essential and one non-essential. We find that inequality between rich and poor dynasties is feasible when (i) the marginal productivity of labor in the production of the essential good is bounded from above and the marginal productivity of capital in the production of the non-essential good is bounded from below by a positive value; and (ii) factor remunerations are not determined by the standard economic forces of marginal product. Under these circumstances, not only income and wealth inequalities are persistent but inequality of consumption between both dynasties is increasing. Simulations indicate that inequality of income and wealth increases with the bargaining power of firms when wages are fixed, and with the parameter of preferences for bequests.